Performance of solar PV micro-grid systems: A comparison study. (July 2018) - Wang, Fu; Zhu, Yingming; Yan, Jinyue
Abstract: Two solar PV micro-grid systems were stablished in this paper to examine and investigate their operation ability according to TOU price. Battery storage was used to adjust the operation strategies and bring in different economic benefits. Heat storage and simulation loads were also chosen to simulate the load variation. The power generation of the PV was comprehensively compared in two locations with different solar resources. The power output from PV systems in Ningbo is higher than that in Sichuan under local climate conditions, the accumulated power generation in Ningbo is 40% more than the power output in Sichuan. A preliminary operation strategy shows that the micro-grid can be continuously operated in the set mode. The battery storage has the capacity to achieve the economic optimization of the micro-grid systems.